Economics - Samuelson, Paul A.; Nordhaus, William D. (New York : McGraw-Hill, 1989)
This book has served as the standard bearer for the teaching of elementary economics since landmark 1984 edition. The thirteenth edition contains an authoritative statement of modern economic science. This edition provides an improved understanding of comparative advantage and international trade, the pricing of products and inputs, the quasi-random movements of stock market, and the principles underlying the determination of national output
Includes index.
Includes bibliographical references.
aia 22/11/2017
Loans
Keywords: Economics